Static, Rigid Dynamics and Computational Fluid Dynamic Simulation of a Zero Co2 and Zero Heat Pollution Compressed Air Engine for the Urban Transport Sector - Tangie Fru, Ngang; Kom K. , Yvan Armel; Nebo K. , Yohan Arnold; Biyeme , Florent; Kanmogne, Abraham (Engineering And Technology Journal, 2024)
This article presents major findings created during a research work for sustainable solutions towards the ozone layer depletion and global warming in the name of modeling and simulating a zero CO2 and zero heat pollution compressed air engine adapted for cities in the Tropics like Cameroon. The static, dynamic and fluid dynamic simulations of the engine conceptual models; products of kinematic and dynamic analyses of the engine realized earlier, led to the adoption of the best engine model for the considered output expectations. This model has for which was set thanks to how the model proved its resistance to extreme static, rigid movements and fluid solicitations. The method used in this work gives room for some flexibility in the designing process of the engine considering it is a systemic transition from expected values to end internal dimensions of the final model.